To look at world by eyes of a phenomenologist - E. A. Tsvetukhina (Омский научный вестник: Серия "Общество. История. Современность")
The article presents an attempt to comprehend basic categories of phenomenology. In modern philosophy, the phenomenological method is almost the only available way in search of authentic existence of the person. Using the phenomenological method, the author reveals the features of human existence, and shows the phenomenological description specifics, to demonstrate force of this method on example of love phenomenon. The article also considers an attempt to comprehend place of the Self in various systems of the phenomenological description. The author comes to the conclusion about force of the phenomenological approach in the looking for the original methodology of understanding the authentic human being